VISITOR SATISFACTION AND REVISIT INTENTIONS: UNDERSTANDING THE EFFECT OF ATTITUDE, ATTRACTIONS, ACCESSIBILITY, AND DESTINATION IMAGE ON WORD OF MOUTH AT KUMALA ISLAND, TENGGARONG - Satryawati; Hamdani; Syachrul; Bela Barus; Sarwo Eddy Wibowo; Tasya Hiana Cecilia (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the effects of attitude, tourism attraction, accessibility, and destination image on word of mouth through visitor satisfaction and revisit intentions at Kumala Island, Tenggarong. A questionnaire was distributed to 162 visitors using an accidental random sampling technique. The study applies a quantitative approach, utilizing path analysis with IBM SPSS Statistics 23 and Structural Equation Modeling (SEM) with AMOS 23 software. Data were measured using a 15-point Likert scale. Before testing the hypothesis, validity and reliability tests were conducted, along with classical assumption tests such as linearity, normality, and multicollinearity. The results show significant impacts of attitude, tourism attraction, accessibility, and destination image on satisfaction and satisfaction on revisit intention. Tourism attraction, accessibility, satisfaction, and revisit intention significantly influence word of mouth. However, the study found no significant effects of attitude, tourism attraction, accessibility, and destination image on revisit intention, nor of attitude and destination image on word of mouth. These findings highlight the importance of visitor satisfaction in influencing revisit intentions and word of mouth while also suggesting some areas where the influence of particular variables is less pronounced.